An efficient synthesis of pyrido[1, 2-a]indoles through aza-Nazarov type cyclization. Issue 9 (17th December 2014) - Karthikeyan, Iyyanar; Arunprasath, Dhanarajan; Sekar, Govindasamy
Abstract : Transition metal free Brønsted acid mediated synthesis of pyrido[1, 2- a ]indole scaffolds has been developed through aza-Nazarov type cyclization of readily available diaryl(2-pyridyl)methanol using formic acid for the synthesis of biologically and medicinally important pyrido[1, 2- a ]indole, indolo[1, 2- a ]quinoline and pyrimido[1, 2- a ]indole derivatives. Abstract : Transition metal free Brønsted acid mediated synthesis of biologically important pyrido[1, 2- a ]indole scaffolds through aza-Nazarov type cyclization of readily available diaryl(2-pyridyl)methanol using formic acid has been developed. This methodology has been successfully extended to synthesize atropisomers.